Effectiveness of giving red spinach on increasing hemoglobin levels in pregnant women in the second trimester with anemia: A literature review - Tuhalauruw, Nelly Enjel (Science Center Group, 2024)
Background: Anemia during pregnancy remains a major global health problem that affects maternal and fetal outcomes. Iron deficiency represents the primary cause of anemia among pregnant women, particularly during the second trimester when iron requirements increase significantly. Dietary approaches using iron-rich vegetables may provide complementary strategies for improving hemoglobin levels. Objective: This study aimed to analyze the effectiveness of red spinach consumption in increasing hemoglobin levels among pregnant women in the second trimester with anemia. Methods: This study used a literature review design following the PRISMA guideline. Articles were identified through systematic searches in Google Scholar and PubMed databases using keywords related to pregnancy, anemia, red spinach, and hemoglobin. The inclusion criteria included studies published between 2018 and 2024, articles written in English or Indonesian, and studies involving pregnant women with anemia receiving red spinach interventions. The SPIDER framework was applied to structure the review process. Data were extracted and synthesized using a narrative approach. Results: Ten studies met the inclusion criteria and were included in the analysis. The studies used experimental and quasi-experimental designs with intervention durations ranging from two to four weeks. Most interventions involved boiled red spinach or red spinach juice. The results consistently showed increased hemoglobin levels among pregnant women after red spinach consumption, with average improvements ranging from approximately 1.1 g/dL to 1.7 g/dL. Conclusion: Red spinach consumption demonstrates potential effectiveness as a nutritional intervention for improving hemoglobin levels among pregnant women with anemia. Incorporating red spinach into maternal dietary programs may support anemia management during pregnancy.